Gateways to art : understanding the visual arts - DeWitte, Debra J.; Larmann, Ralph, 1963-; Shields, M. Kathryn (New York : Thames & Hudson, 2012)
This illustrated new introduction to art examines the visual language of art, how art is made, its history, and how it addresses themes of common concern to humanity from all cultures and eras. Leading artists, scholars, and critics from around the world also provide their own comments on art.--
Includes bibliographical references and index.
Keywords: Art -- Textbooks